'International Law in Ancient China': Eurocentrism and the Rethinking of Case Studies in Chinese Intellectual History. (4th March 2022) - Fan, Xin
ABSTRACT: The opening of the twentieth-first century has been a time of uncertainty. Despite many visions of the future, a Eurocentric bias is still at heart of the discourse about world order. For instance, the 'Thucydides Trap' as a metaphor is often borrowed by political theories to make sense of the changing relationship between China and the United States. Yet as many are turning to ancient history in the 'West' to find wisdom for the future, they tend to overlook the story from the other side of the globe. In this paper, I investigate a genealogy of thought that there existed an international order in ancient China. The concept sounds like an oxymoron to many people today. Yet various scholars have adopted this view as an alternative to the Eurocentric world of international relations over the course of the long twentieth century, from the Western missionary W. A. P. Martin in late Qing, the Chinese historian He Bingsong in the Republican period, to the hawkish PRC foreign policy analyst Yan Xuetong. Recalling this legacy will help us to appreciate the crucial role of political idealism in the reshuffling of international relations in a world that is increasingly leaning towards power politics.